Evaluation of Pain Following the Use of Scalpel versus Diathermy for Skin Incision in Ear, Nose, Throat and Head and Neck Surgeries - Shrestha, Diva (Journal of Nepal Health Research Council, 2018)
Background: Many studies have shown the benefits of diathermy over scalpel for making skin incisions in terms of post operative pain and post operative analgesics requirement. The objective of the study is to compare the pain following incision by scalpel and diathermy for skin in ENT surgery.Methods: We conducted a prospective, randomized study and compared early post operative pain and analgesics requirement in patients undergoing ENT and Head and Neck surgery in Department of ENT at Kathmandu Medical College from September 2016 to August 2017. The statistical analysis was done using MS Excel and SPSS software.Results: Out of 65 participants, 31 were allocated in scalpel group and 30 were allocated in diathermy group. The mean VAS score was significantly greater in scalpel group as compared to diathermy group in post operative 12, 24 and 48 hours (P<0.05). The mean ketorolac requirement was significantly more in scalpel group than in diathermy group in post operative 24 hours. Conclusions: The early post operative pain is less in ENT-Head and Neck surgery patients with skin incision by diathermy as compared to the patients with skin incision by scalpel.